Pre- and postoperative left ventricular contractile function in patients with aortic valve disease. Issue 2 (February 1979) - Krayenbuehl, H P; Turina, M; Hess, O M; Rothlin, M; Senning, A
Abstract : In 43 patients left ventricular micromanometry and cineangiography were performed preoperatively and and 20 months after aortic valve replacement. A score of left ventricular functional impairment, derived from 5 to 8 haemodynamic variables, was calculated as: number of pathological indices x 100/total number of determined indices. Preoperatively the score of left ventricular functional impairment amounted to 35 per cent in group 1 (aortic stenosis: n = 19), to 61 per cent in group 2 (combined lesion:n = 15) (P less than 0.05), and to 87 per cent in group 3 (aortic regurgitation: n = 9) (P less than 0.001). In contrast, the functional classification according to the NYHA showed similar impairment in the 3 groups. Postoperatively the score of left ventricular functional impairment decreased significantly in all 3 groups to 10, 16, and 27 per cent, respectively, but the score of group 3 remained raised (P less than 0.05) as compared with that of group 1. The patients with residual left ventricular dysfunction had a higher preoperative left ventricular muscle mass than the patients with normal or near normal postoperative left ventricular function. It is concluded that (1) at similar functional impairment according to the NYHA classification left ventricular contractile function is more severely impaired in aortic regurgitation and in aortic regurgitation + aortic stenosis than in aortic stenosis alone, (2) left ventricular function improves significantly after valve replacement in all three forms of aortic valve disease, (3) residual functional impairment is greater in aortic regurgitation than in aortic stenosis or aortic stenosis + aortic regurgitation, and (4) persistent postoperative left ventricular functional impairment is found in the patients with severe preoperative hypertrophy.